Effects of fatigue on shootingc performance and biomechanical patterns in elite biathletes - Sattlecker, G.; Buchecker, M.; Birklbauer, J.; Müller, E.; Lindinger, S. J. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
According to scientific studies and expert opinion stance stability, rifle hold, triggering and butt shoulder pressure are considered to be substantial factors influencing shooting scores in biathlon (for references see Sattlecker et al. 2013; Sattlecker et al. 2007). However, corresponding experiments were preliminary conducted without physical preload. Therefore, the aim of the current study was to analyse performance as well as biomechanical shooting patterns in elite biathletes under simulated race conditions.